Infinity and absolutization. An analysis of the meaning of to want and the idols of praxis from the phenomenological method of Maurice Blondel - Pignalitti, David (Pensamiento. Revista de Investigación e Información Filosófica, 2026)
This article proposes an analysis of superstitious practices, of moralism as an ideal of perfection of the act, of metaphysical systems and ideologies as complete and total responses, and of a set of pragmatic phenomena, such as wealth and new technologies, which offer the promise of consummation and fulfillment of human aspiration. From the phenomenological method of L’Action (1893) by Maurice Blondel, it is possible to discover in these phenomena, as modalities of praxis where this takes on an absolutist character, the original dynamism of the will. Said dynamism manifests, in an especially acute way in these phenomena of human activity, the elementary infinite will, which gives reason for the meaning of praxis.